2015
DOI: 10.1007/s10103-015-1749-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photodynamic therapy on Enterococcus faecalis biofilms

Abstract: Microbial biofilms are involved in almost all infectious pathologies of the oral cavity. This has led to the search for novel therapies specifically aimed at biofilm elimination. In this study, we used atomic force microscopy (AFM) to visualize injuries and to determine surface roughness, as well as confocal laser scanning microscopy (CLSM) to enumerate live and dead bacterial cells, to determine the effects of photodynamic therapy (PDT) on Enterococcus faecalis biofilms. The AFM images showed that PDT consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 48 publications
6
34
0
Order By: Relevance
“…These observations were concomitant with the study conducted by López-Jiménez et al [13] which showed the susceptibility of E. faecalis to PDT. They suggested that the antibacterial activity is due to changes in membrane permeability, cell division machinery, and inhibition of bacterial cell wall synthesis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These observations were concomitant with the study conducted by López-Jiménez et al [13] which showed the susceptibility of E. faecalis to PDT. They suggested that the antibacterial activity is due to changes in membrane permeability, cell division machinery, and inhibition of bacterial cell wall synthesis.…”
Section: Discussionsupporting
confidence: 86%
“…As a result, any microorganism, such as E. faecalis, not eradicated and remaining viable at the site of infection would be exposed to doses of PDT that would not result in cell death, i.e., sub-lethal doses of PDT (sPDT), exposing survivors to ROS stress. ROS has been recognized to play an active and important role in processes such as cell death and biofilm/colony development in bacteria [13]. Previous studies have been shown that the exposure of bacteria to sPDT could lead to the extension of resistance to antimicrobial agents and result in an increased risk of poor clinical outcomes, and more consumption of medical resources [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these inactive “ghost” cells was corroborated by the biomass loss assessed by SR assay. Before, it was described that E. faecalis elimination with aPDT resulted in bleb formations suggestive of damage of membrane components (López-Jiménez et al, 2015), shrunken, bacterial cell diameter reduction, rough and fractured appearance of the bacterial cells (Cheng et al, 2012). It was also described the presence of bacterial cell membrane shriveling and alterations including loss of cocci or bacilli shape, grooves on the cell surface and draining of the intracellular components (Garcez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ROS contributes to the microbicidal activity of phagocytes, regulation of signal transduction and gene expression, and induces oxidative damage to nucleic acids, proteins, and lipids . Many evidences have demonstrated the importance of ROS in PDT treatment in both anticancer and antibacterial action . We next measured intracellular ROS generation in S. aureus after treatments.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the antibiotic resistance of biofilm bacteria and planktonic bacteria, more effective antimicrobial agents or new treatments are needed. In recent years, scholars have developed a series of new‐style antibacterial approaches such as nanomolecules , antimicrobial peptide , and photodynamic therapy (PDT) .…”
Section: Introductionmentioning
confidence: 99%